The Link Between Chronic Thromboembolic PulmoChronic thromboembolic pulmonary hypertension (CTEPH) and sarcoidosis are recognized causes of nary Hypertension and Sarcoidosis: Association or Visual Masquerade? - Tandon, Rajive; Baughman, Robert P.; Stanley, Janice; Khan, Ali A (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Chronic thromboembolic pulmonary hypertension (CTEPH) and sarcoidosis are recognized causes of pulmonary hypertension according to the World Health Organization classification scheme. This case series describes seven patients with sarcoidosis with a mean age of 61 who developed pulmonary hypertension. They were found to have CTEPH, diagnosed by either CT pulmonary angiography or a lung ventilation perfusion scan. They all underwent confirmatory right heart catheterization showing elevated mean pulmonary artery pressures (mean of 42 mmHg – normal less than 25 mmHg). Sarcoidosis has been previously shown to be associated with increased rates of venous thromboembolic disease. In these cases, patients with sarcoidosis later developed CTEPH and this may be another mechanism in which sarcoidosis can lead to pulmonary hypertension.